2012
DOI: 10.1038/ejhg.2012.226
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin 2 homozygous mutation in humans with a lethal congenital syndrome

Abstract: Heterozygous mutations in dynamin 2 (DNM2) have been linked to dominant Charcot-Marie-Tooth neuropathy and centronuclear myopathy. We report the first homozygous mutation in the DNM2 protein p.Phe379Val, in three consanguineous patients with a lethal congenital syndrome associating akinesia, joint contractures, hypotonia, skeletal abnormalities, and brain and retinal hemorrhages. In vitro membrane tubulation, trafficking and GTPase assays are consistent with an impact of the DNM2p.Phe379Val mutation on endocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…All DNM2 mutations are either dominant or de novo missense mutations, suggesting a potentially toxic gain-of-function effect produced by the mutations. This hypothesis is supported by the observation that nonsense mutations in DNM2 that result in haploinsufficiency do not cause disease [51]. However, several studies have shown that loss of basic DNM2 functions (such as the regulation of endocytosis) occurs with some mutations, suggesting that loss of function may also contribute to the disease mechanism.…”
Section: What Causes It?mentioning
confidence: 90%
“…All DNM2 mutations are either dominant or de novo missense mutations, suggesting a potentially toxic gain-of-function effect produced by the mutations. This hypothesis is supported by the observation that nonsense mutations in DNM2 that result in haploinsufficiency do not cause disease [51]. However, several studies have shown that loss of basic DNM2 functions (such as the regulation of endocytosis) occurs with some mutations, suggesting that loss of function may also contribute to the disease mechanism.…”
Section: What Causes It?mentioning
confidence: 90%
“…It has been reported that DNM2 gene mutation is an important factor for patients with autosomal dominant centronuclear myopathy (20) and Alzheimer's disease (21,22). Recurrent DNM2 mutations have also been identified in patients with ETP-ALL by whole-exome sequencing (6,10,23). These mutations include: E78fs in the Ras-like GTPase domain; L3354P, R364C, K382E, T404N and E468 * in the dynamin MD domain; S528fs, E544fs and K557_K558>K in the PH domain; S698L in the GTPase effector domain; and K770 * , P791T, L789fs and I805fs in the C-terminus.…”
Section: Discussionmentioning
confidence: 99%
“…LCCS2 is caused by mutation of ERBB3 (Narkis et al, 2007b), a member of the ERBB family of receptor tyrosine kinases; LCCS3 is caused by mutation of PIP5K1C (Narkis et al, 2007a), which encodes phosphatidylinositol-4-phosphate 5-kinase, type I, gamma (PIPKIγ); LCCS5 is caused by homozygous Dynamin 2 (DNM2) mutation (Koutsopoulos et al, 2013); while another study linked mutations in CNTNAP1 (encoding contactin associated protein 1) and ADCY6…”
Section: Introductionmentioning
confidence: 99%